Upaya Guru Meningkatkan Kemampuan Menghafal Surat-Surat Pendek Melalui Metode Tikrar Pada Anak Usia 5-6 Tahun Di Tk Al-Barokah, Sucinaraja-Garut - Widari, Ida; Sugihartini, Iis (LP2M STAI Al-Musaddadiyah Garut, 2025)
The researcher raised the title based on the results of initial observations at Al-Barokah Sucinaraja-Garut Kindergarten regarding the ability to memorize short letters of children aged 5-6 years which showed that it had not yet developed. This research aims to determine the effectiveness of the Tikrar method in improving the ability to memorize short letters in children aged 5 to 6 years at Al-Barokah Kindergarten, Sucinaraja-Garut. This research uses classroom research methods (PTK) carried out in three classroom action research cycles, with a qualitative approach. The object of this research is to improve the ability to memorize short letters for children aged 5-6 years at the Al-Barokah Sucinaraja-Garut Kindergarten, with a total of 10 children. Research results: In cycle I, the first week the researcher began applying the Tikrar method to Surah Al-Lahab, repeated every day for one week in a row in the initial activities before the core of learning, in the second week applying the method to Surah An-Nasr, in cycle II, the third week applying the method. on the Al-Kafirun letter, and in the fourth week of memorization, the memorization is carried out one by one by the children so that the development of memorization abilities can be seen when compared before using the Tikrar method. In the fourth week, the average number of short letters remembered by children increased significantly. shows that the tikrar method is effectively used by teachers to improve the ability to memorize short letters in children aged 5-6 years at Al-Barokah Kindergarten, Sucinaraja-Garut. The application of this method not only increases the number of short letters that are memorized correctly, but also improves children's learning motivation and receives positive responses from parents. Keywords: Effectiveness, Memorization Ability, and Tikrar Method.